KAJIAN PARTISIPASI MAHASISWA TERHADAP LINGKUNGAN FISIK KAMPUS DI POLITEKNIK KESEHATAN KEMENKES SURABAYA - Narwati .; Rusmiati .; Rachmaniyah . (JURNAL PENELITIAN KESEHATAN, 2016)
Community participation is the participation of all community members in solve theproblems of the community. Community participation in the health sector means the participationof all community members in solve the health problems of their own. To cultivate self-awarenessto each of the students is not an easy thing because it is likely to be born of the will of theindividual. Frequently encountered are students too indifferent to the environment, because theythink that the cleanliness of the environment has become the responsibility of a cleaning service.The purpose of this study was to get a description of the student participation onenvironmental cleanliness in Politehnik Kesehatan Kemenkes Surabaya campus.The method used in this research is descriptive, the population in this study is the entireacademic Jurusan Kesehatan Lingkungan Surabaya and Jurusan Gizi is still active, the number of389 students, while the samples are taken using the technique Stratified Random Sampling of 25%of the total population (389 students) then obtained a sample of 98 students. Data collectiontechniques in this study using a questionnaire and wawancara.dan observation data obtained wereanalyzed descriptively that illustrates the participation of students to the cleanliness of the campusJurusan Kesehatan Lingkungan Surabaya and Jurusan Gizi.The results showed that the participation rate of students to the cleanliness of theenvironment on the campus of Jurusan Kesehatan Lingkungan Surabaya and the Jurusan Gizicategory enough (60%), and the participation of students to the cleanliness of the campusincluding the category of moderately active program evaluation activities related to environmentalhygiene in order to follow up the improvement in the future.